Dilema Penggunaan “Syariah” Dalam Deklarasi-Deklarasi HAM Islam - Hudin, Nurul Amin (UIN Sunan Kalijaga Yogyakarta, 2019)
Among the many religions in the world, Islam is the only religion that explicitly declares the notion of human rights known as al-Bayàn al-`Alam ‘an Huqùq al-Insàn fi al-Islàm (Universal Declaration of Human Rights in Islam). Therefore, it is clear that Islam truly respects human rights. However, the use of the term